Nursing Intervention with The Optimalisation of Progressive Muscle Relaxation (PMR) and Range of Motion (ROM) on Blood Pressure and The Functional Ability of Stroke Patient: Case Study - Indriani, Novita; Risdiana, Nurvita (Universitas Muhammadiyah Yogyakarta, 2023)
Introduction – Stroke is the second leading cause of death and the third leading cause of disability in the world and almost 13,7 million will have a stroke each year. Almost 2,1 million Indonesian people experiences stroke. Stroke will influence in functional ability such as hemiparesis or motoric dysfunction. Another pharmacology treatment, non-pharmacology also needed in this situation. The Progressive Muscle Relaxation (PMR) and Range of Motion (ROM) were both of non-pharmacology treatment which can improve the functional ability of stroke patient. Purpose – The purpose of this study is to optimalisation of PMR and ROM on blood pressure and the functional ability of stroke patients. Methodology/Approach – The method used is a case study in one patient with the history of hypertension. The instruments used in this report are a sphygmomanometer to measure blood pressure and a muscle strength scale to measure muscle strength in stroke patients. On the muscle strength scale, a value of 0 indicates complete paralysis and a value of 5 indicates normal muscle strength & normal full range of motion against resistance and full gravity. Findings – There were improvement for functional ability of motoric dysfunction in stroke patients. These finding confirm that the combination between PMR and ROM improved the motoric dysfunction in stroke patients. Originality – This study is an original study in patients with stroke